Automatic Occlusion Removal System using Optical Flow Method - Aneesha, MA; Helen, K.J (International Journal of Computer Sciences and Engineering, 2018)
We present an automatic occlusion removal methodology for occluded images. The occlusion here considered are the images which contain elements such as grid or fence, the reflection of objects through glass windows and raindrop. The appearance of any object in the space which blocks the complete view of another object or a scene considers as the occlusion. Because of occlusion, we lost the aesthetic beauty of the desired scene. To obtain a background scene without any discrepancies occlusion removal is essential. Occlusion may happen accidentally, and also there are some situations we cannot avoid occlusion. For example, taking photos or videos in a zoo, fence removal is impossible. If the fence obstruction removes from photos, the results became awesome. The Aim is to improve the accuracy of occlusion removal system using an optical flow method. The sequence of frames considers as input to the system. The system automatically detects occlusion. The decomposition of the background component and occlusion components are done using an optical flow method. Finally estimates desired background scene while removing the annoying occlusion. We show results of experiments in the various occluded situation while taking photos or videos.